Geopolymer-based artificial stone as well as preparation method and application thereof
By using geological polymer-based artificial stones prepared with single-component geological polymer powder, the problem of high carbon emissions of concrete-based artificial stones is solved, and low-carbon and high-strength material applications are achieved.
Patent Information
- Application Number
- CN202411747078.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-28
AI Technical Summary
Existing concrete-based artificial stones have high carbon emission problems, which limits their promotion and use.
A single-component geological polymer powder is used as the matrix material and prepared by mixing a ball mill of an alkali exciter and a correction material to form a cement-free geological polymer-based artificial stone.
Significantly reduces carbon dioxide emissions, provides materials with high compression and bending strength, while reducing costs, suitable for decorative materials, high temperature resistant lining materials or corrosion-resistant structural materials.
Smart Images

Figure CN119528498A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of artificial stones, and in particular to a geopolymer-based artificial stone and a preparation method and application thereof. Background Art
[0002] In the field of construction and decoration materials, artificial stone is widely used due to its advantages such as beauty, durability and easy processing. Concrete-based artificial stone is a product similar to natural stone made of cement, aggregate, water and additives (such as one or more of retarders, water reducers, early strength agents and expansion agents) through a certain process. Concrete-based artificial stone meets market demand to a certain extent, but the high carbon emissions of cement-based materials limit its promotion and use. Summary of the invention
[0003] The object of the present invention is to provide a geopolymer-based artificial stone and a preparation method and application thereof. The geopolymer-based artificial stone provided by the present invention does not use cement and has significant effects in reducing carbon dioxide emissions. The geopolymer-based artificial stone has high compression strength and bending strength.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a geopolymer-based artificial stone, which does not contain cement and additives, and the preparation raw materials include single-component geopolymer powder, water and aggregate, and the mass ratio of the single-component geopolymer powder, water and aggregate is 1:0.28-0.42:1.5-2.8;
[0006] The single-component geopolymer powder comprises an alkali activator and a corrective material, and the silicon-aluminum ratio of the single-component geopolymer powder is 2 to 3;
[0007] The raw materials for preparing the alkali activator include a high-silicon raw material and an alkali activator, wherein the high-silicon raw material includes quartz sand and / or silica ash with a SiO2 mass content greater than 95%, and the mass ratio of the high-silicon raw material to the alkali activator is 1:1-1.2;
[0008] The corrective material comprises metakaolin and silica fume with a SiO2 mass content greater than 95%.
[0009] Preferably, the alkali activator includes one or more of alkali metal hydroxides, alkali metal carbonates and alkali metal peroxides.
[0010] Preferably, the method for preparing the single-component geopolymer powder comprises the following steps:
[0011] The high silicon raw material and the alkaline activator are first ball-milled and mixed, and then activated to obtain the alkaline activator;
[0012] The alkali activator and the corrective material are mixed by a second ball milling to obtain the single-component geopolymer powder.
[0013] Preferably, the particle size of the ball-milled material obtained after the first ball-milling mixing is ≤0.074 mm;
[0014] The activation treatment temperature is 400-900°C and the holding time is 1-6h;
[0015] The particle size of the single-component geopolymer powder is ≤45 μm.
[0016] Preferably, the aggregate comprises one or more of quartz stone, calcium carbonate and recycled aggregate; the particle size of the aggregate is 0.5-20 mm.
[0017] Preferably, the aggregate includes coarse aggregate and fine aggregate, the particle size of the coarse aggregate is 5-20 mm, the particle size of the fine aggregate is 0.5-5 mm, and the mass ratio of the coarse aggregate to the fine aggregate is 1.2-1.5:1.
[0018] The present invention provides a method for preparing the geopolymer-based artificial stone described in the above technical solution, comprising the following steps:
[0019] Mixing the single-component geopolymer powder, water and aggregate to obtain a slurry;
[0020] The slurry is subjected to molding-curing treatment and curing treatment in sequence to obtain the geopolymer-based artificial stone.
[0021] Preferably, the molding-curing process comprises: placing the slurry in a mold and performing compression molding under vacuum conditions; the compression molding pressure is 1.5×10 5 ~5×10 5 N, holding time is 30~180s.
[0022] Preferably, the curing treatment conditions include: temperature of 20-80° C., relative humidity>90%, and time of 14-28 days.
[0023] The present invention provides the use of the geopolymer-based artificial stone described in the above technical solution or the geopolymer-based artificial stone prepared by the preparation method described in the above technical solution in decorative materials, high temperature resistant lining materials or corrosion resistant structural materials.
[0024] The present invention provides a geopolymer-based artificial stone, which does not contain cement and additives, and the raw materials for preparation include single-component geopolymer powder, water and aggregate, and the mass ratio of the single-component geopolymer powder, water and aggregate is 1:0.28-0.42:1.5-2.8; the single-component geopolymer powder includes an alkali activator and a corrective material, and the silicon-aluminum ratio of the single-component geopolymer powder is 2-3; the raw materials for preparing the alkali activator include high-silicon raw materials and alkali activators, and the high-silicon raw materials include quartz sand and / or silica fume with a SiO2 mass content greater than 95%, and the mass ratio of the high-silicon raw materials to the alkali activator is 1:1-1.2; the corrective material includes metakaolin and silica fume. Compared with traditional concrete-based artificial stones, the geopolymer-based artificial stone provided by the present invention uses single-component geopolymer powder as a matrix material, does not use cement, has significant results in reducing carbon dioxide emissions, provides strong support for promoting green and sustainable development, and does not introduce other types of additives, which is conducive to reducing costs. In addition, the geopolymer-based artificial stone of the present invention has high compressive strength and bending strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The figure is a schematic diagram of the process of preparing geopolymer-based artificial stone in an embodiment of the present invention. DETAILED DESCRIPTION
[0026] The present invention provides a geopolymer-based artificial stone, which does not contain cement and additives, and the preparation raw materials include single-component geopolymer powder, water and aggregate, and the mass ratio of the single-component geopolymer powder, water and aggregate is 1:0.28-0.42:1.5-2.8;
[0027] The single-component geopolymer powder comprises an alkali activator and a corrective material, and the silicon-aluminum ratio of the single-component geopolymer powder is 2 to 3;
[0028] The raw materials for preparing the alkali activator include a high-silicon raw material and an alkali activator, wherein the high-silicon raw material includes quartz sand and / or silica ash with a SiO2 mass content greater than 95%, and the mass ratio of the high-silicon raw material to the alkali activator is 1:1-1.2;
[0029] The corrective material comprises metakaolin and silica fume with a SiO2 mass content greater than 95%.
[0030] In the related art, the raw materials for preparing concrete-based artificial stone include cement, aggregate, water and additives. Concrete-based artificial stone meets the market demand to a certain extent, but the carbon emission of cement-based materials is high, which limits its promotion and use. The present invention uses single-component geopolymer powder as the matrix material, which greatly reduces the carbon emission of traditional cement-based materials and is environmentally friendly. The present invention prepares geopolymer-based artificial stone based on single-component geopolymer powder, water and aggregate, without introducing other types of additives (including but not limited to one or more of retarders, water reducers, early strength agents and expansion agents), and the essential difference between single-component geopolymer powder and cement in material composition and mechanism of action. Specifically, in terms of material composition, the single-component geopolymer powder of the present invention is prepared by alkaline activator and corrective material (i.e., active aluminosilicate), and its skeleton is mainly composed of a three-dimensional network structure formed by aluminum oxide and silicon oxide; while cement is mainly composed of calcium-based materials such as tricalcium silicate and dicalcium silicate, which provide strength by generating calcium silicate hydrate (CSH gel) and calcium hydroxide through hydration reaction. In terms of mechanism of action, the curing of the single-component geopolymer powder of the present invention depends on the dissolution and polycondensation of aluminosilicate under alkaline excitation to form a stable three-dimensional network structure, and its hardening process does not rely on calcium-based hydration products, thus showing excellent chemical and thermal stability; while the hardening of cement generates CSH gel to fill pores through hydration reaction, accompanied by the precipitation of calcium hydroxide. In view of the above differences, the single-component geopolymer powder of the present invention exhibits advantages such as high strength, excellent high temperature resistance and stable chemical properties, wherein the three-dimensional network structure of the geopolymer provides high strength and high durability, so that the geopolymer-based artificial stone has good mechanical properties and chemical corrosion resistance, and can be used for a long time under harsh environmental conditions. In addition, the single-component geopolymer powder is a material that is pre-mixed and processed into a powder, which contains an alkali activator and a geopolymer precursor (i.e., a corrective material), and only water needs to be added when used to form a solid material with high strength and high durability. Compared with the traditional two-component geopolymer system, the single-component geopolymer powder simplifies the storage and transportation of materials, reduces the complexity of the construction process, and has better operability at the construction site. The geopolymer-based artificial stone of the present invention is described in detail below.
[0031] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0032] The raw material for preparing the geopolymer-based artificial stone of the present invention comprises a single-component geopolymer powder. The single-component geopolymer powder is first described in detail below.
[0033] In the present invention, the single-component geopolymer powder includes an alkali activator and a corrective material, and the silicon-aluminum ratio of the single-component geopolymer powder is 2 to 3, specifically 2, 2.2, 2.5, 2.8 or 3. The silicon-aluminum ratio of the present invention specifically refers to the molar ratio of silicon atoms to aluminum atoms in the single-component geopolymer powder. As an embodiment of the present invention, the mass ratio of the alkali activator to the corrective material can be 16 to 18:82 to 84, specifically 17:83.
[0034] In the present invention, the raw materials for preparing the alkaline activator include a high-silicon raw material and an alkaline activator, and the mass ratio of the high-silicon raw material to the alkaline activator is 1:1-1.2, specifically 1:1, 1:1.1 or 1:1.2.
[0035] In the present invention, the high-silicon raw material includes quartz sand and / or silica ash with a SiO2 mass content greater than 95%, specifically quartz sand or silica ash with a SiO2 mass content greater than 95%; in an embodiment of the present invention, the purity of the quartz sand can be ≥97%, the particle size of the quartz sand can be 0.1~1mm, and further can be 0.5~1mm; the SiO2 mass content in the silica ash can specifically be 99.31%, and the particle size of the silica ash can be 0.1~1μm.
[0036] As an embodiment of the present invention, the alkali activator may include one or more of alkali metal hydroxides, alkali metal carbonates and alkali metal peroxides, specifically alkali metal hydroxides, alkali metal carbonates or alkali metal peroxides; the alkali metal hydroxides may include sodium hydroxide and / or potassium hydroxide; the alkali metal carbonates may include sodium carbonate and / or potassium carbonate; the alkali metal peroxide may be sodium peroxide.
[0037] In the present invention, the corrective material includes metakaolin and silica ash with a SiO2 mass content greater than 95%; in an embodiment of the present invention, the Al2O3 content in the metakaolin can be 47.81wt%, the SiO2 content can be 54.31wt%, and the particle size of the metakaolin can be 0.2-5μm; the SiO2 mass content in the silica ash can specifically be 99.31%, and the particle size of the silica ash can be 0.1-1μm. As an embodiment of the present invention, the mass ratio of metakaolin to silica ash in the corrective material can be 38-53:30-44, specifically 53:30, 44:39, 52:31, 43:40, 41:42 or 38:44.
[0038] As an embodiment of the present invention, the method for preparing the single-component geopolymer powder may include the following steps:
[0039] The high silicon raw material and the alkaline activator are first ball-milled and mixed, and then activated to obtain the alkaline activator;
[0040] The alkali activator and the corrective material are mixed by a second ball milling to obtain the single-component geopolymer powder.
[0041] The present invention performs a first ball milling mixing of a high silicon raw material and an alkali activator, and performs an activation treatment to obtain an alkali activator. As an embodiment of the present invention, the particle size of the ball milled material obtained after the first ball milling mixing can be ≤0.074mm. As an embodiment of the present invention, the temperature of the activation treatment can be 400-900°C, specifically 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or 900°C; the insulation time can be 1-6h, specifically 1h, 2h, 3h, 4h, 5h or 6h. In the present invention, the high silicon raw material and the alkali activator are first ball milled and mixed, and the particle size of the material can be refined on the basis of achieving uniform mixing of the two, and the contact area and reaction activity can be increased; then, in a high alkaline environment, the silicon oxygen bond and the aluminum oxygen bond are broken by activation treatment to form silicate monomers and aluminate monomers, providing active sites for subsequent polycondensation reactions.
[0042] After obtaining the alkali activator, the present invention performs a second ball milling mixing of the alkali activator and the corrective material to obtain the single-component geopolymer powder. As an embodiment of the present invention, the single-component geopolymer powder is in powder form, and the particle size of the single-component geopolymer powder can be ≤45μm. In the present invention, the alkali activator and the corrective material are subjected to a second ball milling mixing, which can refine the material particle size and reduce the reaction hindrance between particles on the basis of achieving uniform mixing of the two; and the uniform powder is conducive to the smooth progress of the subsequent polycondensation reaction, so that the formed geopolymer-based artificial stone has consistent performance.
[0043] The raw materials for preparing the geopolymer-based artificial stone of the present invention include aggregates; as an embodiment of the present invention, the aggregates include one or more of quartz, calcium carbonate and recycled aggregates, and can specifically be quartz, calcium carbonate or recycled aggregates; the quartz can specifically be white quartz; the calcium carbonate can specifically be calcium carbonate natural stone; the recycled aggregate can specifically be waste building materials obtained after crushing and screening, and the waste building materials can specifically include one or more of waste concrete, waste ceramics, waste tiles and waste glass; the particle size of the aggregate can be 0.5-20 mm.
[0044] As an embodiment of the present invention, the aggregate may include coarse aggregate and fine aggregate. The particle size of the coarse aggregate may be 5-20 mm, the particle size of the fine aggregate may be 0.5-5 mm, and the mass ratio of the coarse aggregate to the fine aggregate may be 1.2-1.5:1, specifically 1.2:1, 1.3:1, 1.4:1 or 1.5:1.
[0045] The raw material for preparing the geopolymer-based artificial stone of the present invention includes water. The present invention has no special limitation on the water, and water from sources well known to those skilled in the art can be used.
[0046] In the present invention, the mass ratio of the single-component geopolymer powder, water and aggregate is 1:0.28-0.42:1.5-2.8, wherein the mass ratio of the single-component geopolymer powder to water is 1:0.28-0.42, specifically 1:0.28, 1:0.3, 1:0.32, 1:0.33, 1:0.34, 1:0.36, 1:0.38, 1:0.4 or 1:0.42; the mass ratio of the single-component geopolymer powder to aggregate is 1:1.5-2.8, specifically 1:1.5, 1:1.8, 1:2, 1:2.2, 1:2.5 or 1:2.8.
[0047] The present invention provides a method for preparing the geopolymer-based artificial stone described in the above technical solution, comprising the following steps:
[0048] Mixing the single-component geopolymer powder, water and aggregate to obtain a slurry;
[0049] The slurry is subjected to molding-curing treatment and curing treatment in sequence to obtain the geopolymer-based artificial stone.
[0050] The present invention mixes a single-component geopolymer powder, water and aggregate to obtain a slurry. In the present invention, the single-component geopolymer powder, water and aggregate are mixed, and the silicate monomer and the aluminate monomer in the single-component geopolymer powder undergo a polycondensation reaction under alkaline conditions to gradually form a geopolymer with a three-dimensional network structure; the addition of aggregate can not only provide a structural skeleton and enhance the overall mechanical properties, but also reduce the risk of shrinkage and cracks. As an embodiment of the present invention, the mixing can be stirring mixing, and stirring mixing can ensure the uniformity of the slurry and prevent local differences in material properties.
[0051] After obtaining the slurry, the present invention sequentially performs molding-curing treatment and curing treatment on the slurry to obtain the geopolymer-based artificial stone. As an embodiment of the present invention, the molding-curing treatment may include: placing the slurry in a mold and performing press molding under vacuum conditions; in the embodiment of the present invention, specifically, the slurry is placed in a prefabricated mold, and then a high-frequency vibrator is used to vibrate at a frequency of 25 to 50 kHz for 30 to 180 seconds to expel bubbles, and then a hydraulic press is used to align the mold, and after vacuum is extracted, press molding is performed; the pressure of the press molding may be 1.5×10 5 ~5×10 5 N, specifically, can be 2.2×10 5N; the holding time can be 30 to 180 seconds, specifically 30 seconds. As an embodiment of the present invention, demolding is performed after the molding-curing treatment is completed, and then curing treatment is performed; the conditions of the curing treatment may include: a temperature of 20 to 80°C, specifically room temperature; a relative humidity of >90%, specifically 93%; a time of 14 to 28 days, specifically 28 days. In the present invention, during the molding-curing treatment of the slurry, the geopolymer gradually forms a stable solid structure through a condensation reaction, and the curing treatment can effectively promote the transformation of the gel phase to the solid phase, improve the density and mechanical properties of the material, and reduce the generation of pores and microcracks.
[0052] As an embodiment of the present invention, the curing treatment may further include grinding and polishing in sequence. The present invention has no special limitation on the specific manner of the grinding and polishing, and the manners familiar to those skilled in the art may be adopted.
[0053] The present invention provides the use of the geopolymer-based artificial stone described in the above technical solution or the geopolymer-based artificial stone prepared by the preparation method described in the above technical solution in decorative materials, high temperature resistant lining materials or corrosion resistant structural materials. As an embodiment of the present invention, the decorative material may specifically include decorative materials for kitchen countertops, bathroom counters, floors or walls; the high temperature resistant lining material may specifically be an industrial kiln lining material; the corrosion resistant structural material may specifically be a structural material for a strong acid chemical pool.
[0054] The present invention uses a single-component geopolymer powder as a matrix material, which greatly reduces the carbon emissions of traditional cement-based materials and is environmentally friendly. The single-component geopolymer powder formula of the present invention is optimized so that the material can reach high strength in a shorter period of time, and exhibits a lower shrinkage rate and excellent chemical corrosion resistance during the curing process, thereby enhancing the durability and applicability of the geopolymer-based artificial stone. In addition, the present invention utilizes the high temperature resistance of the single-component geopolymer powder so that the geopolymer-based artificial stone can remain stable in a high temperature environment, thereby expanding its scope of application. Therefore, the present invention provides a high-performance, low-cost and environmentally friendly geopolymer-based artificial stone, which brings new options to the field of construction and decorative materials.
[0055] Figure 1 The schematic diagram of the process of preparing geopolymer-based artificial stone in the embodiment of the present invention is shown below. The technical scheme in the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] The raw materials used in the following examples include: metakaolin (Al2O3 content is 47.81wt%, SiO2 content is 54.31wt%; particle size is 0.2-5μm); silica fume (SiO2 content is 99.31wt%; particle size is 0.1-1μm); flaky sodium hydroxide (purity is 97%); quartz sand (purity is 97%; particle size is 0.5-1mm); the aggregate is white quartz stone, and the aggregate includes coarse aggregate (particle size is 5-20mm) and fine aggregate (particle size is 0.5-5mm), and the mass ratio of the coarse aggregate to the fine aggregate is 1.5:1.
[0057] Example 1
[0058] Quartz sand and flaky sodium hydroxide are mixed in a mass ratio of 1:1, and ball-milled in a ball mill until the particle size of the material is less than 0.074 mm. The obtained ball-milled material is placed in a rotary kiln and activated at 500° C. for 6 hours to obtain an alkali activator;
[0059] The alkaline activator, metakaolin and silica fume are mixed in a mass ratio of 17:53:30 (the total silicon-aluminum ratio is 2), and ball milled in a ball mill until the material particle size is less than 45 μm to obtain a single-component geopolymer powder;
[0060] The single-component geopolymer powder, water and aggregate (specifically quartz stone) are mixed in a mass ratio of 1:0.3:2.8, and stirred evenly using a concrete mixer to obtain a slurry;
[0061] The slurry was poured into a prefabricated cubic mold (length, width and height were all 70 mm), and vibrated for 30 s at a frequency of 25 kHz using a high-frequency vibrator to expel bubbles. The cubic mold was then placed on a hydraulic press, vacuum was drawn and 2.2×10 5 The pressure of N was maintained for 30 seconds to complete the pressing and forming; then the stone was placed in a curing box with a relative humidity of 93% and cured at room temperature for 28 days to obtain a geopolymer-based artificial stone.
[0062] Example 2
[0063] Quartz sand and flaky sodium hydroxide are mixed in a mass ratio of 1:1, and ball-milled in a ball mill until the particle size of the material is less than 0.074 mm. The obtained ball-milled material is placed in a rotary kiln and activated at 600° C. for 6 hours to obtain an alkali activator;
[0064] The alkaline activator, metakaolin and silica fume are mixed in a mass ratio of 17:44:39 (the total silicon-aluminum ratio is 2.5), and ball milled in a ball mill until the material particle size is less than 45 μm to obtain a single-component geopolymer powder;
[0065] The single-component geopolymer powder, water and aggregate (specifically quartz stone) are mixed in a mass ratio of 1:0.32:2.8, and stirred evenly using a concrete mixer to obtain slurry;
[0066] The slurry was poured into a prefabricated cubic mold (length, width and height were all 70 mm), and vibrated for 30 s at a frequency of 25 kHz using a high-frequency vibrator to expel bubbles. The cubic mold was then placed on a hydraulic press, vacuum was drawn and 2.2×10 5 The pressure of N was maintained for 30 seconds to complete the pressing and forming; then the stone was placed in a curing box with a relative humidity of 93% and cured at room temperature for 28 days to obtain a geopolymer-based artificial stone.
[0067] Example 3
[0068] Quartz sand and flake sodium hydroxide are mixed in a mass ratio of 1:1.1, and ball-milled in a ball mill until the particle size of the material is less than 0.074 mm. The obtained ball-milled material is placed in a rotary kiln and activated at 500° C. for 6 hours to obtain an alkali activator;
[0069] The alkaline activator, metakaolin and silica fume are mixed in a mass ratio of 17:52:31 (the total silicon-aluminum ratio is 2), and ball milled in a ball mill until the material particle size is less than 45 μm to obtain a single-component geopolymer powder;
[0070] The single-component geopolymer powder, water and aggregate (specifically quartz stone) are mixed in a mass ratio of 1:0.34:2.8, and stirred evenly using a concrete mixer to obtain a slurry;
[0071] The slurry was poured into a prefabricated cubic mold (length, width and height were all 70 mm), and vibrated for 30 seconds at a frequency of 26 kHz using a high-frequency vibrator to expel bubbles. The cubic mold was then placed on a hydraulic press, vacuum was drawn and 2.2×10 5 The pressure of N was maintained for 30 seconds to complete the pressing and forming; then the stone was placed in a curing box with a relative humidity of 93% and cured at room temperature for 28 days to obtain a geopolymer-based artificial stone.
[0072] Example 4
[0073] Quartz sand and flaky sodium hydroxide are mixed in a mass ratio of 1:1.1, and ball-milled in a ball mill until the particle size of the material is less than 0.074 mm. The obtained ball-milled material is placed in a rotary kiln and activated at 600° C. for 6 hours to obtain an alkali activator;
[0074] The alkaline activator, metakaolin and silica fume are mixed in a mass ratio of 17:43:40 (the total silicon-aluminum ratio is 2.5), and ball milled in a ball mill until the material particle size is less than 45 μm to obtain a single-component geopolymer powder;
[0075] The single-component geopolymer powder, water and aggregate (specifically quartz stone) are mixed in a mass ratio of 1:0.33:2.8, and stirred evenly using a concrete mixer to obtain a slurry;
[0076] The slurry was poured into a prefabricated cubic mold (length, width and height were all 70 mm), and vibrated for 30 seconds at a frequency of 25 kHz using a high-frequency vibrator to expel bubbles. The 70 mm cubic mold was then placed on a hydraulic press, vacuum was drawn and a 2.2 × 10 5 The pressure of N was maintained for 30 seconds to complete the pressing and forming; then the stone was placed in a curing box with a relative humidity of 93% and cured at room temperature for 28 days to obtain a geopolymer-based artificial stone.
[0077] Example 5
[0078] Quartz sand and flaky sodium hydroxide are mixed in a mass ratio of 1:1.2, and ball-milled in a ball mill until the particle size of the material is less than 0.074 mm. The obtained ball-milled material is placed in a rotary kiln and activated at 450° C. for 6 hours to obtain an alkali activator;
[0079] The alkaline activator, metakaolin and silica fume are mixed in a mass ratio of 17:41:42 (the total silicon-aluminum ratio is 2.5), and ball milled in a ball mill until the material particle size is less than 45 μm to obtain a single-component geopolymer powder;
[0080] The single-component geopolymer powder, water and aggregate (specifically quartz stone) are mixed in a mass ratio of 1:0.38:2.8, and stirred evenly using a concrete mixer to obtain a slurry;
[0081] The slurry was poured into a prefabricated cubic mold (length, width and height were all 70 mm), and vibrated for 30 seconds at a frequency of 25 kHz using a high-frequency vibrator to expel bubbles. The 70 mm cubic mold was then placed on a hydraulic press, vacuum was drawn and a 2.2 × 10 5 The pressure of N was maintained for 30 seconds to complete the pressing and forming; then the stone was placed in a curing box with a relative humidity of 93% and cured at room temperature for 28 days to obtain a geopolymer-based artificial stone.
[0082] Example 6
[0083] Quartz sand and flake sodium hydroxide are mixed in a mass ratio of 1:1.2, and ball-milled in a ball mill until the material particle size is less than 0.074 mm. The obtained ball-milled material is placed in a rotary kiln and activated at 500° C. for 6 hours to obtain an alkali activator;
[0084] The alkaline activator, metakaolin and silica fume are mixed in a mass ratio of 17:38:44 (the total silicon-aluminum ratio is 3), and ball milled in a ball mill until the material particle size is less than 45 μm to obtain a single-component geopolymer powder;
[0085] The single-component geopolymer powder, water and aggregate (specifically quartz stone) are mixed in a mass ratio of 1:0.42:2.8, and stirred evenly using a concrete mixer to obtain a slurry;
[0086] The slurry was poured into a prefabricated cubic mold (length, width and height were all 70 mm), and vibrated for 30 seconds at a frequency of 25 kHz using a high-frequency vibrator to expel bubbles. The 70 mm cubic mold was then placed on a hydraulic press, vacuum was drawn and a 2.2 × 10 5 The pressure of N was maintained for 30 seconds to complete the pressing and forming; then the stone was placed in a curing box with a relative humidity of 93% and cured at room temperature for 28 days to obtain a geopolymer-based artificial stone.
[0087] Test Example 1
[0088] The samples cured for different times in Examples 1 to 6 were subjected to performance tests, specifically, compression strength tests according to the test specified in GB / T 35160.3 and bending performance tests according to the test specified in GB / T 35160.2. The results are shown in Table 1. As can be seen from Table 1, the test results of the samples cured for different times in Examples 1 to 6 are all higher than the national standards.
[0089] Table 1 Performance test results of samples cured for different time periods in Examples 1 to 6
[0090]
[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A geopolymer-based artificial stone, free of cement and additives, wherein the raw materials for preparation include single-component geopolymer powder, water and aggregate, wherein the mass ratio of the single-component geopolymer powder, water and aggregate is 1:0.28-0.42:1.5-2.8; The single-component geopolymer powder comprises an alkali activator and a corrective material, and the silicon-aluminum ratio of the single-component geopolymer powder is 2 to 3; The raw materials for preparing the alkali activator include a high-silicon raw material and an alkali activator, wherein the high-silicon raw material includes quartz sand and / or silica ash with a SiO2 mass content greater than 95%, and the mass ratio of the high-silicon raw material to the alkali activator is 1:1-1.2; The corrective material comprises metakaolin and silica fume with a SiO2 mass content greater than 95%.
2. The geopolymer-based artificial stone according to claim 1, characterized in that: The alkali activator includes one or more of alkali metal hydroxides, alkali metal carbonates and alkali metal peroxides.
3. The geopolymer-based artificial stone according to claim 1 or 2, characterized in that: The method for preparing the single-component geopolymer powder comprises the following steps: The high silicon raw material and the alkaline activator are first ball-milled and mixed, and then activated to obtain the alkaline activator; The alkali activator and the corrective material are mixed by a second ball milling to obtain the single-component geopolymer powder.
4. The geopolymer-based artificial stone according to claim 3, characterized in that: The particle size of the ball-milled material obtained after the first ball-milling mixing is ≤0.074 mm; The activation treatment temperature is 400-900°C and the holding time is 1-6h; The particle size of the single-component geopolymer powder is ≤45 μm.
5. The geopolymer-based artificial stone according to claim 1, characterized in that: The aggregate comprises one or more of quartz stone, calcium carbonate and recycled aggregate; the particle size of the aggregate is 0.5-20 mm.
6. The geopolymer-based artificial stone according to claim 1 or 5, characterized in that: The aggregate comprises coarse aggregate and fine aggregate, the particle size of the coarse aggregate is 5-20 mm, the particle size of the fine aggregate is 0.5-5 mm, and the mass ratio of the coarse aggregate to the fine aggregate is 1.2-1.5:
1.
7. The method for preparing the geopolymer-based artificial stone according to any one of claims 1 to 6, comprising the following steps: Mixing the single-component geopolymer powder, water and aggregate to obtain a slurry; The slurry is subjected to molding-curing treatment and curing treatment in sequence to obtain the geopolymer-based artificial stone.
8. The preparation method according to claim 7, characterized in that: The molding-curing process includes: placing the slurry in a mold and performing compression molding under vacuum conditions; the compression molding pressure is 1.5×10 5 ~5×10 5 N, holding time is 30~180s.
9. The preparation method according to claim 7, characterized in that: The curing treatment conditions include: temperature of 20-80° C., relative humidity>90%, and time of 14-28 days.
10. Use of the geopolymer-based artificial stone according to any one of claims 1 to 6 or the geopolymer-based artificial stone prepared by the preparation method according to any one of claims 7 to 9 in decorative materials, high temperature resistant lining materials or corrosion resistant structural materials.